Sexual self-efficacy and sexual quality of life before and after laparoscopic surgery in women with endometriosis lesions: A cross-sectional study - Soraya Malekmaleki; Shadab Shahali; Ashraf Moini (International Journal of Reproductive BioMedicine, 2022)
Abstract Background: Endometriosis is one of the most common gynecological diseases and is associated with an increased risk of dyspareunia. Objective: This study aimed to evaluate sexual self-efficacy (SSE) and sexual quality of life (SQOL) before and after laparoscopic surgery of endometriosis lesions. Materials and Methods: This cross-sectional study measured the dependent variable by questionnaires before and after the surgery, and was performed with 36 women with endometriosis (aged 20-40 yr) who were referred to Arash hospital, Tehran, Iran between December 2018 and July 2019 using a convenience sampling method. Data collection tools included SQOL and SSE questionnaires, and a visual analogue scale. Data were collected before, and 3 and 6 months after laparoscopic surgery. Results: Out of the 36 women included in this study, 91.7% had pelvic endometriosis and 8.3% had abdominal and pelvic endometriosis. 9 participants (25.0%) were in stages I or II of the disease, and 29 (75.0%) had endometriosis with higher involvement. The findings of the study showed a positive effect of laparoscopic surgery on SQOL and SSE in participants (p < 0.001). Conclusion: Laparoscopic surgery in cases of endometriosis can improve SQOL and SSE in affected women and improve dyspareunia.